Active Microstructured Optical Arrays of Grazing Incidence Reflectors. (14th July 2010) - Willingale, Richard; Feldman, Charlotte; Michette, Alan; Button, Tim; Dunare, Camelia; Folkard, Melvyn; Hart, David; McFaul, Chris; Morrison, Graeme R.; Parkes, William; Pfauntsch, Sławka; Powell, A. Keith; et al.
Abstract : The UK Smart X-Ray Optics (SXO) programme is developing active/adaptive optics for terrestrial applications. One of the technologies proposed is microstructured optical arrays (MOAs), which focus X-rays using grazing incidence reflection through consecutive aligned arrays of microscopic channels. Although such arrays are similar in concept to polycapillary and microchannel plate optics, they can be bent and adjusted using piezoelectric actuators providing control over the focusing and inherent aberrations. Custom configurations can be designed, using ray tracing and finite element analysis, for applications from sub-keV to several-keV X-rays, and the channels of appropriate aspect ratios can be made using deep silicon etching. An exemplar application will be in the microprobing of biological cells and tissue samples using TiK α radiation (4.5 keV) in studies related to radiation-induced cancers. This paper discusses the optical design, modelling, and manufacture of such optics.